THE IMPLEMENTATION OF “PROJECT APPROACH” BY LILIAN G. KATZ TO IMPROVING RELIGION AND MORAL, ALSO LANGUAGE DEVELOPMENT - Izzati, Khoerul; Syamsudin, Amir Syamsudin; Christianti, Martha (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This study discusses the importance of the “Project Approach” in early childhood education, which involves activities outside the classroom so that children are involved in conducting observations, interviews and site visits to explore project topics. The results show that direct involvement in real experiences improves children's understanding of the subject matter. In addition, creative representations, such as drawing and modeling, allow children to express their understanding in a variety of ways. The effectiveness of this approach is seen from the increase in children's involvement and motivation in learning, as well as the development of social and communication skills in language. This study supports a more interactive and applied learning approach in early childhood education.